EXPERIENCE IN THE IMPLEMENTATION OF THE PARENTAL ENLIGHTENMENT PROGRAM "AXIOMS OF PARENTAL LOVE" - Petrash, Elena; Sidorova, Tatyana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
It’s not easy to parents of schoolchildren in the modern conditions of lack of time and understanding, that’s why the school today must engage actively in parental enlightenment. The parent club represents as interactive form of acquiring psychological and pedagogical knowledge and enriching the parents’ educational experience. The research purpose is to study the impact of interruptions of parent-child relationships on the development of the child’s personality and to show how to prevent them. The program, which is implemented in the Lyceum No. 8 of the Pskov city, is based on the statement that children growing up in an atmosphere of love and understanding have fewer problems related to health, communication with peers, education, etc. The club’s work includes: discussion meetings, evenings of "Questions and Answers", trainings, playing problem situations, questioning, game exercises, games - relaxation, games - dramatization.